(untitled) (Research, Society and Development, 2021)
Nature offers a wide chemical diversity. Thus, plants represent an important source of new substances, mainly due to secondary metabolites. Geraniol is an acyclic isoprenoid monoterpene isolated from aromatic plant essential oils. Geraniol’s diverse activities suggest that this molecule could treat various diseases as a promising drug candidate. To assess the potential of geraniol applied in a clinical trial, this review aims to provide a comprehensive summary of the pharmacological effects of geraniol. The retrieved publications Pubmed / NCBI, Science Direct, SCIELO and Google Scholar were collected and summarized between the years 2013 to 2021. Next, the potential application of geraniol as a medicine is discussed based on its pharmacological properties, including antitumor, anti-inflammatory, antioxidant and antimicrobial activities and hepatoprotective effects. Therefore, it is noteworthy that future investigations can significantly contribute to the follow-up of works with the GOH, making it possible to assess its pharmacological potential.